A hybrid approach to achieve organizational agility: An empirical study of a food company. Issue 1 (5th February 2018) - Nejatian, Majid; Zarei, Mohammad Hossein; Nejati, Mehran; Zanjirchi, Seyed Mahmood
Abstract : Purpose: In today's intense global competition, agility is advocated as a fundamental characteristic for business survival and competitiveness. The purpose of this paper is to propose a practical methodology to achieve and enhance organizational agility based on strategic objectives. Design/methodology/approach: In the first step, a set of key performance indicators (KPIs) of the organization being studied are recognized and classified under the perspectives of balanced scorecard (BSC). Critical success factors are then identified by ranking the KPIs according to their importance in achieving organizational strategic objectives using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). In the second step, three houses of quality (HOQs) are constructed sequentially to identify and rank the main agile attributes, agile enablers, and improvement paths. In addition, in order to translate linguistics judgments of practitioners into numerical values in building HOQs, fuzzy logic is employed. Findings: The capability of the proposed methodology is demonstrated by applying it to a case of a multi-national food company in Iran. Through the application, the company could find the most suitable improvement paths to improve its organizational agility. Research limitations/implications: A limited number of KPIs were chosen due to computational and visual constraints related to HOQs. Another limitation, similar to other agility studies, which facilitate decision making among agility metrics, was that the metrics were more industry-specific and less inclusive. Practical implications: A strong practical advantage for the application of the methodology over directly choosing agility metrics without linking them is that through the methodology, the right metrics were selected that match organization's core values and marketing objectives. While metrics may ostensibly seem unrelated or inappropriate, they actually contributed to the right areas where there were gaps between the current and desired level of agility. It would otherwise be impossible to choose the right metrics without a structured methodology. Originality/value: This paper proposes a novel methodology for achieving organizational agility. By utilizing and linking several tools such as BSC, fuzzy TOPSIS, and quality function deployment (QFD), the proposed approach enables organizations to identify the most appropriate agile attributes, agile enablers, and subsequently agile improvement paths.